2013
DOI: 10.4161/auto.25132
|View full text |Cite|
|
Sign up to set email alerts
|

Cerebral ischemia-reperfusion-induced autophagy protects against neuronal injury by mitochondrial clearance

Abstract: Cerebral ischemia-reperfusion (I-R) is a complex pathological process. Although autophagy can be evoked by ischemia, its involvement in the reperfusion phase after ischemia and its contribution to the fate of neurons remains largely unknown. In the present investigation, we found that autophagy was activated in the reperfusion phase, as revealed in both mice with middle cerebral artery occlusion and oxygen-glucose deprived cortical neurons in culture. Interestingly, in contrast to that in permanent ischemia, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
394
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 444 publications
(436 citation statements)
references
References 51 publications
39
394
2
1
Order By: Relevance
“…Mild oxidative stress specifically triggers mitophagy in a Drp1-dependent manner (45). Recent studies have applied Mdivi-1, a pharmacological inhibitor of Drp1, for the study of mitophagy (28)(29)(30)(31). Here, we confirmed that CSE regulated Drp1 in pulmonary epithelial cells.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Mild oxidative stress specifically triggers mitophagy in a Drp1-dependent manner (45). Recent studies have applied Mdivi-1, a pharmacological inhibitor of Drp1, for the study of mitophagy (28)(29)(30)(31). Here, we confirmed that CSE regulated Drp1 in pulmonary epithelial cells.…”
Section: Discussionsupporting
confidence: 78%
“…We used Mdivi-1, a known inhibitor of mitochondrial fission, as a tool to study the relationships between mitophagy and mitochondrial dysfunction. Although Mdivi-1 is characterized as a pharmacological inhibitor of Drp1, recent studies have also implicated Mdivi-1 as an inhibitor of mitophagy (28)(29)(30)(31). We first tested the efficacy of this compound as an inhibitor of mitochondrial fission in response to CSE.…”
Section: Resultsmentioning
confidence: 99%
“…However, when lysosome inhibitors were applied, LC3-II protein levels failed to elevate indicating an autophagic-flux impairment in the hippocampus ). An upregulation in LC3-II protein levels was also observed during reperfusion after 1 h of transient MCAO, but in this case no changes in the autophagic-flux were observed in the penumbra region (Zhang et al, 2013a). This discrepancy may be due to the differences in the methodology used to induce brain ischemia (global vs focal ischemia) and or to intrinsic properties of the brain region analysed, which was different in the two sets of experiments.…”
Section: Autophagy In Brain Ischemiamentioning
confidence: 79%
“…This discrepancy may be due to the differences in the methodology used to induce brain ischemia (global vs focal ischemia) and or to intrinsic properties of the brain region analysed, which was different in the two sets of experiments. The class III phosphoinositide 3-kinase (PI3K) inhibitor 3-methyladenine (3-MA), a wellknown inhibitor of autophagosome expansion thus inhibiting autophagy, further increased the infarct volume after transient MCAO and reinforced apoptotic cell death 24 h after OGD in cultured cerebrocortical neurons (Zhang et al, 2013a). This increase in vulnerability to OGD in the presence of 3-MA was due to the defective mitochondrial clearance by the autophagic pathway thus failing in aborting apoptosis (Adhami et al, 2007;Zhang et al, 2013a).…”
Section: Autophagy In Brain Ischemiamentioning
confidence: 99%
See 1 more Smart Citation